El cuidado y la mujer-cuidadora: su construcción televisiva en los programas de salud en Colombia. - Alejandro, Agudelo-Calle (Hacia la Promoción de la Salud)
Introduction: Television has played (and continues to play) an important role in the production of meanings around health and care. More and more television programs are emerging that, from their different formats (soap operas, newscasts, magazines, etc.), address the relationship between both concepts from different angles and narratives. Objective: to reveal how, through some programs focused on health, Colombian television represents care. Methodology: Qualitative with an exploratory scope. A textual analysis of 68 episodes of three Colombian television programs between 2013 and 2014 was carried out and 10 producers of audiovisual health content were interviewed. Results: these shows demonstrated that such programs place care within the framework of disease prevention and health promotion, a context in which the "housewife" woman plays a central role because she is the "natural recipient" of the audiovisual content. However, while health programs make women responsible for the care of themselves and others, at the same time they delegitimize their knowledge in the face of the specialized technical knowledge of biomedical health professionals. Conclusion: producers and television messages reproduce and naturalize the feminization of care.